Speaking Difficulties Factors faced by Non-English Students - N. Erna Marlia Susfenti (Integrative Perspectives of Social and Science Journal, 2026)
This study examines the factors that contribute to English speaking difficulties among non-English Department students. Although English is an important skill in academic and professional contexts, many non-English Department students face obstacles in mastering English speaking skills. The main factors that contributed to speaking difficulties included psychological factors, linguistic factors and social environment factor. This study used a qualitative approach with a case study design, involving 90 from Islamic Civilization and History students at UIN Sultan Maulana Hasanuddin Banten. Data were collected through in-depth interviews and questionnaires that focused on students' perceptions and experiences related to speaking difficulties. The results of the analysis showed that the difficulties factor faced by students is linguistic factors with 58%, psyichological factor with 27% and social environment with 15%. Therefore, teaching factors that were less focused on speaking skills and more theory-oriented methods also contributed to these difficulties. This study suggests that English teaching at the tertiary level should pay more attention to developing speaking skills through more intensive practice and approaches that support students' self-confidence. These findings are expected to be a reference for educators and policy makers in designing a more effective curriculum to improve the speaking skills of non-English Department students.